An Alternative Approach to Atopic Dermatitis: Part II—Summary of Cases and Discussion. Issue 2 (2004) - Kobayashi, Hiromi; Takahashi, Kuniaki; Mizuno, Nobuyuki; Kutsuna, Haruo; Ishii, Masamitsu
Abstract : In the first part of this Review, we presented case-series where Kampo treatment was introduced for those atopic dermatitis (AD) patients who had failed with conventional therapy, in an attempt to prove that there exists a definite subgroup of AD patients for whom Kampo treatment is effective. In this second part, we will first provide the summary of the results for 140 AD patients we treated in 2000. The results suggest that Kampo treatment is effective for more than half of AD patients who fail with conventional therapy. In the Discussion, we will examine the evidential basis for conventional AD therapy and discuss how Kampo treatment should be integrated into the guidelines for AD therapy. We contend that Kampo treatment should be tried before systematic immunosuppressive agents are considered. As each Kampo treatment is highly individualized, it should be regarded more as 'art' than technology, and special care should be taken to assess its efficacy in clinical trial.